2021
DOI: 10.2147/cmar.s299157
|View full text |Cite
|
Sign up to set email alerts
|

Value of Combining Clinical Factors, Conventional Ultrasound, and Contrast-Enhanced Ultrasound Features in Preoperative Prediction of Central Lymph Node Metastases of Different Sized Papillary Thyroid Carcinomas

Abstract: Purpose Early and accurate preoperative diagnosis of central lymph node metastasis (CLNM) is crucial to improve surgical management of patients with clinical lymph node-negative papillary thyroid carcinoma (PTC). Towards improving diagnosis of CLNM, we assessed the value of combining preoperative clinical characteristics, conventional ultrasound, and contrast-enhanced ultrasound (CEUS) in preoperative prediction of CLNM of different sized PTCs. Patients and Methods Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 44 publications
4
12
5
1
Order By: Relevance
“…( 36 ) reported that old age was a risk factor of LNMs. Multifocality has been reported to be associated with an increased risk of LNMs ( 8 , 32 , 37 , 38 ) and it was identified to be an independent risk factor of microscopic pN1 in our study.…”
Section: Discussionsupporting
confidence: 66%
“…( 36 ) reported that old age was a risk factor of LNMs. Multifocality has been reported to be associated with an increased risk of LNMs ( 8 , 32 , 37 , 38 ) and it was identified to be an independent risk factor of microscopic pN1 in our study.…”
Section: Discussionsupporting
confidence: 66%
“…The nomogram model was established using the seven independent risk predictors: gender, age, multifocality, tumor size, extracapsular invasion, boundary, and US suggested CLNM (Figure 3). The model score axis (2)(3)(4)(5)(6)(7)(8)(9) corresponded to the score of each predictor from bottom to top, and then the total score was calculated to find the risk of CLNM corresponding to the last risk axis. The C-index of the nomogram was 0.940 (95% CI, 0.888-0.991), suggesting that the nomogram model has a favorable prediction performance of CLNM.…”
Section: Establishment Of Nomogram Modelmentioning
confidence: 99%
“…PTC is more common in female patients, and the incidence rate in women is three times that in men. Although PTC is considered to be an indolent tumor with low malignancy, slow disease progression, and good prognosis ( 2 ), 20–50% of patients still have early cervical lymph node metastasis (CLNM), leading to a high risk of local recurrence ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…The six largest studies regarding differentiation between benign and metastatic cervical lymp nodes, conducted between 2014 and 2019, show that CEUS has a good diagnostic accuracy superior to standard US and Color-Doppler grayscale alone [ 59 , 74 , 77 , 78 , 79 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In particular: L/S ratio < 2, ill-defined margins, hyper-echogenicity, cystic necrosis, calcification and peripheral vascularity are found at baseline US; meanwhile, centripetal or asynchronous perfusion (Figure 2a,b), non-or hyper-enhancement, perfusion defects and ring enhancing margins are found using CEUS; lymph nodes with one or more of the previous features are considered metastatic [77]. The six largest studies regarding differentiation between benign and metastatic cervical lymp nodes, conducted between 2014 and 2019, show that CEUS has a good diagnostic accuracy superior to standard US and Color-Doppler grayscale alone [59,74,[77][78][79] (Table 1). 3 The study divides patients into two groups, PTC (>10mm), PTMC (<10mm); 4 The evaluation is based on a prediction model combining both the parameters obtained from the CEUS and clinical parameters.…”
Section: Evaluation Of Lymph-node Local Staging Using Ceusmentioning
confidence: 99%